El humanismo en Educación Inica ldel centro de estimulación temprana¨Baby City¨ - Duque Ortiz, Ana Cristina (2023)
This research was developed as a response to the problem that was evident at "Baby City" early and prenatal stimulation center, located in Riobamba city, Chimborazo province; the topic investigated was "Humanism in Initial Education" at Baby City early stimulation center. The lack of knowledge of humanism in initial education by teachers and parents was notorious, for that reason, the study was carried out with the objective of developing immediate actions so that it is of vital interest in the education of children both at home and in the classroom. To carry out this research, a general objective and two specific objectives were proposed, furthermore, it was supported by the development of a theoretical framework, it was a basic and field investigation for the reason that was executed at the scene of the events and there was direct contact with the study subjects, the design of the research was non-experimental in consideration that the variables were not manipulated in the study, the level of research was documentary therefore the information was collected from various digital repositories, books , magazines, among others. Two research techniques were used: the observation using an observation form as an instrument directed at children; and the other technique was the survey using a sheet as an instrument aimed at parents and teachers; allowing a situational diagnosis of the reality allowed to determine the main causes of the problem, where it was possible to analyze that both teachers and parents should know humanism in initial education in a theoretical and practical way and include it in the process of education in a constant way to obtain an excellent integral development in children and allow them to build their identity.